2014
DOI: 10.4102/jef.v7i2.151
|View full text |Cite
|
Sign up to set email alerts
|

Happiness among first-year students at a comprehensive tertiary institution: An exploratory study

Abstract: The 1970s saw a significant increase in the volume of research on individuals’ subjective experience of well-being. The subjective well-being of university students has received less attention, however. Student well-being is important, given the widespread concern over the high dropout rates at institutions of higher learning in South Africa (Council of Higher Education, 2013; Van Zyl, 2010). The paper adds to the existing body of literature through an exposition on the possible influence of variables forthcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Within this approach, numerous prior studies have investigated the determinants of quality of life (QoL) or subjective well-being amongst university and college students; however, this is mostly within a developed country context (Botha, Snowball, De Klerk & Radloff, 2013;Pretorius & Blaauw, 2014). Even in developed countries, the fulfilment of basic needs is the cornerstone of explaining students' subjective well-being (Türkdoğan & Duru, 2012).…”
Section: Relevant Literature: Students and Subjective Well-beingmentioning
confidence: 99%
See 4 more Smart Citations
“…Within this approach, numerous prior studies have investigated the determinants of quality of life (QoL) or subjective well-being amongst university and college students; however, this is mostly within a developed country context (Botha, Snowball, De Klerk & Radloff, 2013;Pretorius & Blaauw, 2014). Even in developed countries, the fulfilment of basic needs is the cornerstone of explaining students' subjective well-being (Türkdoğan & Duru, 2012).…”
Section: Relevant Literature: Students and Subjective Well-beingmentioning
confidence: 99%
“…Variables endogenous to the institutions refer to issues such as living conditions, social spaces, leisure activities and the culture on campus (Botha et al, 2013). Pretorius and Blaauw (2014) conducted an exploratory study on the subjective well-being of first-year students at a comprehensive higher education institution. Apart from the elements highlighted by previous international and local studies, they found additional variables in particular that are of importance for first-year students' subjective well-being.…”
Section: Relevant Literature: Students and Subjective Well-beingmentioning
confidence: 99%
See 3 more Smart Citations